An alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal, a preparation method and application thereof
Patent Information
- Application Number
- CN202610765731.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-29
AI Technical Summary
更为不利的是,这些缺陷及其畸变区域可能会俘获电子形成色心,导致晶体在特定工作波段的光吸收系数显著增加,最终严重制约了晶体的光学透过率和激光损伤阈值
(1)本发明中采用碱土金属(Ca或Mg)与硅(Si)离子进行异价共掺杂,对铽钪铝石榴石磁光晶体实现协同调控;具体的:通过二价碱土金属优先占据十二面体或八面体格位,Si4+优先占据四面体格位,在晶格内部形成完美的局域电荷补偿,从根本上阻断了氧空位等色心缺陷的产生;同时,利用掺杂离子对多面体尺寸的协同调控作用及SiO键的高键合强度,能够优化晶格畸变、增强晶体骨架稳定性、缓解热应力累积,从根本上解决铽钪铝石榴石磁光晶体易开裂的技术难题。
Smart Images

Figure CN122466560B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of laser crystal materials technology, specifically to a terbium-scandium-aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon, its preparation method, and its application. Background Technology
[0002] Currently, commercially available magneto-optical crystals are mainly terbium gallium garnet (Tb3Ga5O4). 12 Terbium gallium garnet (TGG) crystals are used, but in high-power laser environments, terbium gallium garnet crystals suffer from strong thermal lensing and thermally induced depolarization effects, making them unsuitable for higher-power laser systems. In contrast, terbium scandium aluminum garnet (Tb3Sc2Al3O4) crystals... 12 TSAG crystals have advantages such as higher Verdet constant, excellent thermal conductivity and high laser damage threshold, making them ideal candidate materials for next-generation high-power magneto-optical isolators.
[0003] Despite the excellent magneto-optical properties of terbium-scandium-aluminum garnet crystals, their internal quality is often constrained by multiple factors during actual growth and application. Firstly, the high melting point of terbium-scandium-aluminum garnet crystals means that during high-temperature growth and subsequent cooling, the crystal undergoes complex temperature gradient changes, leading to significant thermal stress accumulation and greatly increasing the risk of crystal cracking, thus affecting practical applications. Secondly, terbium-scandium-aluminum garnet crystals have a cubic garnet structure, and the internal Tb content... 3+ ,Sc 3+ And Al 3+ Significant differences in ionic radius and coordination environment between plasmas lead to polyhedral size mismatch, causing the lattice tolerance factor to deviate from the ideal stable range. This easily induces local structural instability and severe microscopic lattice distortion, not only degrading crystal quality but also becoming a major microscopic cause of crystal cracking. Furthermore, the crystal growth process is accompanied by the generation of intrinsic defects such as oxygen vacancies and antisite defects, severely affecting crystal quality. The aforementioned macroscopic thermal stress, microscopic lattice distortion, and internal crystal defects are coupled together, severely damaging the integrity of the crystal structure. Even more detrimental is that these defects and their distorted regions may trap electrons to form color centers, leading to a significant increase in the light absorption coefficient of the crystal in specific operating wavelengths, ultimately severely limiting the optical transmittance and laser damage threshold of the crystal. Summary of the Invention
[0004] To overcome the above problems, this invention provides a terbium scandium aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon, its preparation method, and its application.
[0005] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a terbium-scandium-aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon, having the molecular formula (Tb 1-x Ca x )3Sc2(Al 1-z Si z )3O 12 Or Tb3(Sc 1-y Mg y )2(Al 1-z Si z )3O 12 , where x = z, 0 < x < 0.1; 2y = 3z, 0 < y < 0.1.
[0006] The alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal belongs to the cubic garnet structure with space group Ia-3d; wherein, Ca 2+ Occupying dodecahedral sites, Mg 2+ Occupying the octahedral position, Si 4+ It occupies a tetrahedral position.
[0007] A second aspect of the present invention provides a method for preparing the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal described in the first aspect, comprising the following steps: Based on the molecular formula of the terbium scandium aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon, the raw materials are obtained according to the stoichiometric ratio. The raw materials are mixed evenly, pressed into blocks, and then solid-state sintered to obtain polycrystalline material. Place the polycrystalline material into a crucible and then into a single-crystal furnace. In an oxygen-free atmosphere, heat the material using medium-frequency induction heating until the polycrystalline material melts and the melt is homogeneously mixed. The seed crystal is placed into the melt, and the crystal pulling is completed by sequentially going through crystal pulling, necking, shoulder formation, equal diameter formation and tailing. Once the crystal has grown to the specified size, it is pulled out to detach from the melt, the temperature is lowered to room temperature, and the crystal is removed. After the crystal is cut into devices, it is annealed to obtain a terbium scandium aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon.
[0008] In one or more embodiments, based on the molecular formula (Tb) of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal... 1-x Ca x )3Sc2(Al 1-z Si z )3O 12 The raw materials include Tb4O7, Sc2O3, Al2O3, CaCO3, and SiO2; Based on the molecular formula Tb3(Sc) of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal...1-y Mg y )2(Al 1- z Si z )3O 12 The raw materials include Tb4O7, Sc2O3, Al2O3, MgO and SiO2.
[0009] In one or more embodiments, the solid-state sintering temperature is 1300~1500℃ and the sintering time is 24~60 h.
[0010] In one or more embodiments, the crucible is an iridium crucible. Iridium crucibles combine ultra-high melting point, excellent chemical inertness, high-temperature strength, excellent thermal shock resistance and oxidation resistance, and can be directly induction heated to create an ideal single crystal growth environment.
[0011] In one or more embodiments, the oxygen-free atmosphere includes nitrogen or a rare gas.
[0012] In one or more embodiments, medium-frequency induction heating is used until the polycrystalline material melts, at a temperature of 1950~2000℃.
[0013] In one or more embodiments, the seed crystal is <111> Defect-free oriented seed crystals, including terbium scandium aluminum garnet (Tb3Sc2Al3O4). 12 Crystal.
[0014] In one or more embodiments, during the crystal pulling process, the pulling rate is 0.2~3 mm / h and the rotation speed is 8~30 rpm.
[0015] In one or more embodiments, the cooling rate during the process of lowering the temperature to room temperature is 10~80°C / h. Slow cooling can reduce thermal stress.
[0016] In one or more embodiments, the annealing atmosphere is an air atmosphere.
[0017] In one or more embodiments, the annealing temperature is 1300~1500℃ and the annealing time is 20~30 h.
[0018] A third aspect of the present invention provides the application of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal described in the first aspect or the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared by the preparation method described in the second aspect as a magneto-optical device material, including any one of the following: Used in Faraday isolators; Used in magneto-optical modulation devices; Alternatively, it can function as a magneto-optical crystal that acts as a magneto-optical switch.
[0019] The beneficial effects of this invention are as follows: (1) In this invention, alkaline earth metals (Ca or Mg) and silicon (Si) ions are co-doped in opposite valences to achieve synergistic control of the terbium-scandium-aluminum garnet magneto-optical crystal; specifically: by having divalent alkaline earth metals preferentially occupy dodecahedral or octahedral lattice sites, Si 4+ Preferentially occupying tetrahedral lattice sites, perfect local charge compensation is formed within the lattice, fundamentally blocking the generation of color center defects such as oxygen vacancies; simultaneously, the synergistic control of polyhedral size by doped ions and Si... The high bonding strength of the O bonds can optimize lattice distortion, enhance the stability of the crystal skeleton, and alleviate the accumulation of thermal stress, fundamentally solving the technical problem of easy cracking of terbium scandium aluminum garnet magneto-optical crystals.
[0020] (2) The terbium scandium aluminum garnet magneto-optical crystal co-doped with alkaline earth metal and silicon prepared by the present invention has high integrity, no cracks, few internal defects, and excellent optical uniformity. It has low absorption loss in the visible to near-infrared working band and excellent magneto-optical performance, which can well meet the requirements of high-power laser systems. It has important industrial application prospects in the new generation of high-power Faraday optical isolators. Attached Figure Description
[0021] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0022] Figure 1 The Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb) prepared in Example 1) 0.999 Ca 0.001 )3Sc2(Al 0.999 Si 0.001 )3O 12 (A picture of the actual product) Figure 2 The Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb) prepared in Example 2) 0.998 Ca 0.002 )3Sc2(Al 0.998 Si 0.002 )3O 12 (A picture of the actual product) Figure 3 The Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc)) prepared in Example 3 0.99985 Mg 0.00015 )2(Al 0.9999 Si 0.0001 )3O 12 (A picture of the actual product) Figure 4 Terbium scandium aluminum garnet (Tb3Sc2Al3O) prepared in Comparative Example 2 12 A physical image of a TSAG crystal; Figure 5 The terbium scandium aluminum garnet magneto-optical crystals co-doped with alkaline earth metals and silicon prepared in Examples 1-3 and the terbium scandium aluminum garnet (Tb3Sc2Al3O4) prepared in Comparative Example 2 are examples of such crystals. 12 X-ray powder diffraction (XRD) pattern of the crystal; Figure 6 The terbium scandium aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon prepared in Example 1 and the terbium scandium aluminum garnet (Tb3Sc2Al3O4) prepared in Comparative Example 2 are examples of such crystals. 12 Diagram showing the internal residual stress distribution of the crystal; Figure 7 The terbium scandium aluminum garnet magneto-optical crystals co-doped with alkaline earth metals and silicon prepared in Examples 1-2 and the terbium gallium garnet (Tb3Ga5O) prepared in Comparative Example 1 are examples of crystals prepared in Comparative Example 1. 12 Comparison of light absorption in crystals.
[0023] Figure 8 The alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared in Example 1 and the terbium gallium garnet (Tb3Ga5O) prepared in Comparative Example 1 are examples of such crystals. 12 Comparison of Verdet constants of crystals. Detailed Implementation
[0024] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0025] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0026] Despite the excellent magneto-optical properties of terbium-scandium-aluminum garnet crystals, their internal quality is often constrained by multiple factors during actual growth and application. Firstly, the high melting point of terbium-scandium-aluminum garnet crystals means that during high-temperature growth and subsequent cooling, the crystal undergoes complex temperature gradient changes, leading to significant thermal stress accumulation and greatly increasing the risk of crystal cracking, thus affecting practical applications. Secondly, terbium-scandium-aluminum garnet crystals have a cubic garnet structure, and the internal Tb content...3+ ,Sc 3+ And Al 3+ Significant differences in ionic radius and coordination environment between plasmas lead to polyhedral size mismatch, causing the lattice tolerance factor to deviate from the ideal stable range. This easily induces local structural instability and severe microscopic lattice distortion, not only degrading crystal quality but also becoming a major microscopic cause of crystal cracking. Furthermore, the crystal growth process is accompanied by the generation of intrinsic defects such as oxygen vacancies and antisite defects, severely affecting crystal quality. The aforementioned macroscopic thermal stress, microscopic lattice distortion, and internal crystal defects are coupled together, severely damaging the integrity of the crystal structure. Even more detrimental is that these defects and their distorted regions may trap electrons to form color centers, leading to a significant increase in the light absorption coefficient of the crystal in specific operating wavelengths, ultimately severely limiting the optical transmittance and laser damage threshold of the crystal.
[0027] To improve the internal defects and enhance the optical quality of magneto-optical crystals, ion doping engineering is often employed. Currently, the modification of terbium-scandium-aluminum garnet crystals mainly focuses on equivalent ion doping (such as introducing Ga). 3+ (or other trivalent rare earth ions). However, such equivalent doping modification has obvious limitations: on the one hand, equivalent doping cannot provide effective charge compensation and is difficult to suppress intrinsic defects such as oxygen vacancies; on the other hand, a single equivalent ion can only achieve local or unidirectional polyhedral control, and it is difficult to fundamentally correct the inherent polyhedral size mismatch of the terbium-scandium-aluminum garnet lattice. If a single heterovalent ion is used for doping, although some structural control may be achieved, it is easy to destroy the lattice domain electrical neutrality, induce new compensation defects, and even deteriorate the optical homogeneity of the crystal.
[0028] To overcome the above problems, this invention provides a complete, crack-free, low-defect, and low-absorption-loss alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal and its preparation method.
[0029] The stable formation of garnet structures depends on the matching degree between the charge configuration of ions at each polyhedral lattice site and the ideal ionic radius. This invention overcomes the limitations of single-equivalent ion doping modification by employing heterovalent co-doping of alkaline earth metals (Ca or Mg) and silicon (Si) ions to achieve synergistic control of terbium-scandium-aluminum garnet magneto-optical crystals. Specifically, by introducing divalent alkaline earth metals and tetravalent nonmetals with specific radii, based on ionic radius and coordination preference, they preferentially occupy dodecahedral, octahedral, and tetrahedral lattice sites, respectively. This co-doping system not only achieves perfect charge compensation at the local microscopic level, cutting off the generation pathway of oxygen vacancies and fundamentally blocking the generation of color center defects such as oxygen vacancies; but also utilizes the synergistic control effect of dopant ions on polyhedral size and Si… The high bonding strength of O bonds can optimize lattice distortion, enhance the stability of the crystal framework, alleviate the accumulation of thermal stress, optimize the distortion stress and color center defects inside the crystal, and comprehensively improve the mechanical and optical properties of the crystal.
[0030] Furthermore, the alkaline earth metal and silicon co-doped system provided by this invention does not introduce unnecessary absorption peaks and perfectly preserves the extremely high Verdet constant of the matrix material itself.
[0031] Furthermore, this invention employs the mature Czochralski method to grow heterovalently co-doped terbium-scandium-aluminum garnet magneto-optical crystals, requiring no complex modifications to existing commercial crystal growth equipment. The operation is relatively simple, with a short and controllable production cycle. The prepared crystals are intact and crack-free, exhibiting extremely high optical uniformity, excellent magneto-optical properties, and good machinability. This significantly accelerates the commercial mass production of large-size, high-quality Faraday optical isolators for next-generation high-power laser systems. Simultaneously, the modified doping materials used are not only safe and non-toxic but also extremely inexpensive and readily available on the market, significantly reducing the production cost of high-end magneto-optical crystals.
[0032] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0033] Example 1 Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb 0.999 Ca 0.001 )3Sc2(Al 0.999 Si 0.001 )3O 12 Preparation of ) (1) Based on the Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb 0.999 Ca 0.001 )3Sc2(Al 0.999 Si 0.001 )3O 12 The molecular formula of the raw materials is obtained according to the stoichiometric ratio. The raw materials consist of Tb4O7, Sc2O3, Al2O3, CaCO3 and SiO2, and the initial purity of the raw materials is 99.99%.
[0034] (2) Put the raw materials into a mixer and mix them thoroughly for 48 h; after mixing, press them into cylindrical blocks using a hydraulic press, place them in a corundum crucible, and calcine them in a sintering furnace at 1350℃ for 48 h to obtain polycrystalline material.
[0035] (3) The polycrystalline material is loaded into a clean iridium crucible and placed in a single crystal furnace. Under an argon atmosphere, it is heated by medium-frequency induction heating and kept at a constant temperature of about 10 °C above the melting point (1970 °C) for 2 hours to fully homogenize the melt.
[0036] (4) Slowly lower the seed crystal, i.e., terbium scandium aluminum garnet (Tb3Sc2Al3O4), into the crystal. 12 The seed crystal is then introduced, and the seed temperature is adjusted (2-5℃ higher than the melting point (1970℃)) to allow the seed crystal to slightly melt and shrink to a diameter of 2-3 mm. After the crystal pulling is completed, the automatic control program is entered, sequentially completing shoulder formation, equal diameter formation, and tailing to complete the crystal pulling. Growth parameters: pulling speed is 2 mm / h, and rotation speed is 15 rpm.
[0037] (5) After the crystal grows to the specified size, pull the crystal out to separate it from the melt, and slowly cool it to room temperature at a rate of 30℃ / h, and then take out the crystal.
[0038] (6) After the crystal is cut into devices, it is annealed in a high-temperature air atmosphere: the temperature is raised to 1400℃ and held for 24 h, and then cooled to room temperature at a rate of 30℃ / h to obtain Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb 0.999 Ca 0.001 )3Sc2(Al 0.999 Si 0.001 )3O 12 ).
[0039] Example 2 Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb 0.998 Ca 0.002 )3Sc2(Al 0.998 Si 0.002 )3O 12 Preparation of ) (1) Based on the Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb 0.998 Ca 0.002 )3Sc2(Al 0.998 Si 0.002 )3O 12 The molecular formula of the raw materials is obtained according to the stoichiometric ratio. The raw materials consist of Tb4O7, Sc2O3, Al2O3, CaCO3 and SiO2, and the initial purity of the raw materials is 99.99%.
[0040] (2) Put the raw materials into a mixer and mix them thoroughly for 36 h; after mixing, press them into cylindrical blocks using a hydraulic press, place them in a corundum crucible, and calcine them in a sintering furnace at 1350℃ for 36 h to obtain polycrystalline material.
[0041] (3) The polycrystalline material is loaded into a clean iridium crucible and placed in a single crystal furnace. Under an argon atmosphere, it is heated by medium-frequency induction heating and kept at a constant temperature of about 10 °C above the melting point (1970 °C) for 2 hours to fully homogenize the melt.
[0042] (4) Slowly lower the seed crystal, i.e., terbium scandium aluminum garnet (Tb3Sc2Al3O4), into the crystal. 12 The seed crystal is then introduced, and the seed temperature is adjusted (2-5℃ higher than the melting point (1970℃)) to allow the seed crystal to slightly melt and shrink to a diameter of 2-3 mm. After the crystal pulling is completed, the automatic control program is entered, sequentially completing shoulder formation, equal diameter formation, and tailing to complete the crystal pulling. Growth parameters: pulling speed is 1 mm / h, and rotation speed is 20 rpm.
[0043] (5) After the crystal grows to the specified size, pull the crystal out to separate it from the melt, and slowly cool it to room temperature at a rate of 25℃ / h, and then take out the crystal.
[0044] (6) After the crystal is cut into devices, it is annealed in a high-temperature air atmosphere: the temperature is raised to 1400℃ and held for 24 h, and then cooled to room temperature at a rate of 30℃ / h to obtain Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb 0.998 Ca 0.002 )3Sc2(Al 0.998 Si 0.002 )3O 12 ).
[0045] Example 3 Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc) 0.99985 Mg 0.00015 )2(Al 0.9999 Si 0.0001 )3O 12 Preparation of ) (1) Based on Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc 0.99985 Mg 0.00015 )2(Al 0.9999 Si 0.0001 )3O 12 The molecular formula of the raw materials is obtained according to the stoichiometric ratio. The raw materials consist of Tb4O7, Sc2O3, Al2O3, MgO and SiO2, and the initial purity of the raw materials is 99.99%.
[0046] (2) Put the raw materials into a mixer and mix them thoroughly for 40 h; after the mixing is completed, press them into cylindrical blocks using a hydraulic press, place them in a corundum crucible, and calcine them in a sintering furnace at 1350℃ for 50 h to obtain polycrystalline material.
[0047] (3) The polycrystalline material is loaded into a clean iridium crucible and placed in a single crystal furnace. Under an argon atmosphere, it is heated by medium-frequency induction heating and kept at a constant temperature of about 10 °C above the melting point (1970 °C) for 2 hours to fully homogenize the melt.
[0048] (4) Slowly lower the seed crystal, i.e., terbium scandium aluminum garnet (Tb3Sc2Al3O4), into the crystal. 12 The seed crystal is then introduced, and the seed temperature is adjusted (2-5℃ higher than the melting point (1970℃)) to allow the seed crystal to slightly melt and shrink to a diameter of 2-3 mm. After the crystal pulling is completed, the automatic control program is entered, sequentially completing shoulder formation, equal diameter formation, and tailing to complete the crystal pulling. Growth parameters: pulling speed is 1 mm / h, and rotation speed is 12 rpm.
[0049] (5) After the crystal grows to the specified size, pull the crystal out to separate it from the melt, and slowly cool it to room temperature at a rate of 25℃ / h, and then take out the crystal.
[0050] (6) After the crystal is cut into devices, it is annealed in a high-temperature air atmosphere: the temperature is raised to 1400℃ and held for 24 h, and then cooled to room temperature at a rate of 30℃ / h to obtain Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc 0.99985 Mg 0.00015 )2(Al 0.9999 Si 0.0001 )3O 12 ).
[0051] Example 4 Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc) 0.9985 Mg 0.0015 )2(Al 0.999 Si 0.001 )3O 12 Preparation of ) (1) Based on Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc 0.9985 Mg 0.0015 )2(Al 0.999 Si 0.001 )3O 12 The molecular formula of the raw materials is obtained according to the stoichiometric ratio. The raw materials consist of Tb4O7, Sc2O3, Al2O3, MgO and SiO2, and the initial purity of the raw materials is 99.99%.
[0052] (2) The raw materials are put into a mixer and mixed thoroughly for 40 h. After the mixing is completed, the mixture is pressed into a cylindrical block by a hydraulic press, placed in a corundum crucible, and calcined in a sintering furnace at 1450℃ for 30 h to obtain polycrystalline material.
[0053] (3) The polycrystalline material is loaded into a clean iridium crucible and placed in a single crystal furnace. Under an argon atmosphere, it is heated by medium-frequency induction heating and kept at a constant temperature of about 10 °C above the melting point (1970 °C) for 2 hours to fully homogenize the melt.
[0054] (4) Slowly lower the seed crystal, i.e., terbium scandium aluminum garnet (Tb3Sc2Al3O4), into the crystal. 12 The seed crystal is then introduced, and the seed temperature is adjusted (2-5℃ higher than the melting point (1970℃)) to allow the seed crystal to slightly melt and shrink to a diameter of 2-3 mm. After the crystal pulling is completed, the automatic control program is entered, sequentially completing shoulder formation, equal diameter formation, and tailing to complete the crystal pulling. Growth parameters: pulling speed is 1 mm / h, and rotation speed is 18 rpm.
[0055] (5) After the crystal grows to the specified size, pull the crystal out to separate it from the melt, and slowly cool it to room temperature at a rate of 15℃ / h, and then take out the crystal.
[0056] (6) After the crystal is cut into devices, it is annealed in a high-temperature air atmosphere: the temperature is raised to 1400℃ and held for 24 h, and then cooled to room temperature at a rate of 30℃ / h to obtain Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc 0.9985 Mg 0.0015 )2(Al 0.999 Si 0.001 )3O 12 ).
[0057] Comparative Example 1 Terbium gallium garnet (Tb3Ga5O) 12 Crystal preparation: According to the molecular formula Tb3Ga5O 12 The raw materials (Tb4O7 and Ga2O3) required for crystal growth were weighed according to the stoichiometric ratio, and the initial purity of the raw materials was 99.99%.
[0058] The raw materials are put into a mixer and mixed thoroughly for 40 hours. After mixing, the mixture is pressed into a cake shape by a hydraulic press and then sintered in a muffle furnace at 1350°C for 48 hours to obtain polycrystalline material.
[0059] Subsequently, following steps (3) and (4) in Example 1, terbium gallium garnet (Tb3Ga5O) was prepared. 12 In step (3), the seed crystal is terbium gallium garnet (Tb3Ga5O4). 12 Crystal.
[0060] Comparative Example 2 Terbium scandium aluminum garnet (Tb3Sc2Al3O) 12 Crystal preparation: (1) According to terbium scandium aluminum garnet (Tb3Sc2Al3O 12 The molecular formula of the crystal is obtained by obtaining the raw materials according to the stoichiometric ratio. The raw materials are composed of Tb4O7, Sc2O3 and Al2O3, and the initial purity of the raw materials is 99.99%.
[0061] (2) Put the raw materials into a mixer and mix them thoroughly for 48 hours. After mixing, press them into a cake shape using a hydraulic press, place them in a corundum crucible, and calcine them in a sintering furnace at 1350°C for 60 hours to obtain polycrystalline material.
[0062] (3) The polycrystalline material is loaded into a clean iridium crucible and placed in a single crystal furnace. Under an argon atmosphere, it is heated by medium-frequency induction heating and kept at a constant temperature of about 10 °C above the melting point (1970 °C) for 2 hours to fully homogenize the melt.
[0063] (4) Slowly lower the seed crystal, i.e., terbium scandium aluminum garnet (Tb3Sc2Al3O4), into the crystal. 12 The seed crystal is then introduced, and the seed temperature is adjusted (2-5℃ higher than the melting point (1970℃)) to allow the seed crystal to slightly melt and shrink to a diameter of 2-3 mm. After the crystal pulling is completed, the automatic control program is entered, sequentially completing shoulder formation, equal diameter formation, and tailing to complete the crystal pulling. Growth parameters: pulling speed is 2 mm / h, and rotation speed is 15 rpm.
[0064] (5) After the crystal grows to the specified size, pull the crystal out to separate it from the melt, and slowly cool it to room temperature at a rate of 30℃ / h, and then take out the crystal.
[0065] (6) After the crystal is cut into devices, it is annealed in a high-temperature air atmosphere: the temperature is raised to 1400℃ and held for 24 h, and then cooled to room temperature at a rate of 30℃ / h to obtain terbium scandium aluminum garnet (Tb3Sc2Al3O4). 12 Crystal.
[0066] Experimental Example 1 Figure 1 The Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb) prepared in Example 1) 0.999 Ca 0.001 )3Sc2(Al 0.999 Si 0.001 )3O 12 (A picture of the actual product) Figure 2 The Ca-Si co-doped terbium scandium aluminum garnet magneto-optical crystal ((Tb) prepared in Example 2) 0.998 Ca 0.002 )3Sc2(Al 0.998 Si 0.002 )3O 12 (A picture of the actual product) Figure 3 The Mg-Si co-doped terbium scandium aluminum garnet magneto-optical crystal (Tb3(Sc)) prepared in Example 3 0.99985 Mg 0.00015 )2(Al 0.9999 Si 0.0001 )3O 12(A picture of the actual product) Figure 4 Terbium scandium aluminum garnet (Tb3Sc2Al3O) prepared in Comparative Example 2 12 A physical image of a TSAG crystal.
[0067] By comparison Figures 1-4 It can be seen that the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystals prepared in Examples 1-3 are complete and transparent in appearance, without cracking, and have no obvious macroscopic cracks or inclusions inside, exhibiting extremely high crystal quality; in contrast, the terbium scandium aluminum garnet (Tb3Sc2Al3O) in Comparative Example 2... 12 The crystal exhibited severe macroscopic cracking. This significant contrast strongly confirms that the heterovalent co-doping strategy of this invention can effectively reduce microscopic lattice distortion through the synergistic effect of multiple lattice sizes, and introduce strong covalent bonds (Si-O bonds) to enhance the rigidity of the crystal lattice domains, effectively solving the problem of terbium-scandium aluminum garnet (Tb3Sc2Al3O) crystals. 12 The technical challenge of crystals being extremely prone to cracking.
[0068] Experiment Example 2 Figure 5 The terbium scandium aluminum garnet magneto-optical crystals co-doped with alkaline earth metals and silicon prepared in Examples 1-3 and the terbium scandium aluminum garnet (Tb3Sc2Al3O4) prepared in Comparative Example 2 are examples of such crystals. 12 X-ray powder diffraction (XRD) pattern of the crystal, from Figure 5 As can be seen from the XRD patterns of the alkaline earth metal and silicon co-doped crystals prepared in Examples 1-3 and the terbium scandium aluminum garnet (Tb3Sc2Al3O4) magneto-optical crystal prepared in Comparative Example 2, the XRD patterns of the terbium scandium aluminum garnet (Tb3Sc2Al3O4) magneto-optical crystals prepared in Examples 1-3 are significantly different from those of the terbium scandium aluminum garnet 12 The peaks of the standard diffraction spectrum of the crystal are basically consistent, and no impurity peaks appear. Therefore, the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared in this invention has good crystallinity and no impurity phases.
[0069] Experimental Example 3 The alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared in Example 1 and the terbium scandium aluminum garnet (Tb3Sc2Al3O4) prepared in Comparative Example 2 12 The internal residual stress distribution of the crystal is as follows: Figure 6 As shown. From Figure 6 As can be seen from the results, the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared in Example 1 exhibits a lighter white interference color under a polarimeter, indicating that the residual stress inside the crystal is extremely small, its extinction performance is good, and it possesses excellent optical homogeneity and macroscopic structural stability. In contrast, the undoped pure terbium scandium aluminum garnet (Tb3Sc2Al3O4) prepared in Comparative Example 2... 12The crystal exhibits dense and distinct colored interference fringes, indicating that there is extremely severe thermal stress concentration and local lattice distortion inside.
[0070] Experiment Example 4 Figure 7 The terbium scandium aluminum garnet magneto-optical crystals co-doped with alkaline earth metals and silicon prepared in Examples 1-2 and the terbium gallium garnet (Tb3Ga5O) prepared in Comparative Example 1 are examples of crystals prepared in Comparative Example 1. 12 Comparison of light absorption in crystals.
[0071] Depend on Figure 7 It can be seen that the terbium scandium aluminum garnet magneto-optical crystals co-doped with alkaline earth metals and silicon prepared in Examples 1 and 2 have significantly lower absorption values than the terbium gallium garnet (Tb3Ga5O) prepared in Comparative Example 1. 12 This result demonstrates that by introducing alkaline earth metals and silicon ions for synergistic substitution, a perfect charge self-compensating environment is constructed within the crystal lattice, fundamentally blocking the generation pathways of color center defects such as oxygen vacancies. Therefore, the terbium-scandium-aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon completely eliminates the additional absorption caused by intrinsic defects, significantly reducing optical loss and meeting the extremely stringent low absorption requirements of magneto-optical isolator dielectric materials for next-generation high-power laser systems.
[0072] Experimental Example 5 Figure 8 The alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared in Example 1 and the terbium gallium garnet (Tb3Ga5O) prepared in Comparative Example 1 are examples of such crystals. 12 Comparison of Verdet constants of crystals.
[0073] Depend on Figure 8 It can be seen that the Verdet constants of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared in Example 1 are significantly higher than those of the terbium gallium garnet (Tb3Ga5O) in Comparative Example 1 in different wavelength bands. 12 The terbium-scandium-aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon prepared in Example 1 achieves a Verdet constant of 263 rad·m at a wavelength of 532 nm. -1 ·T -1 Compared to terbium gallium garnet (Tb3Ga5O) in Comparative Example 1 at the same wavelength... 12 The crystal performance was improved by 15.4%; at the 1064 nm wavelength commonly used in high-power laser systems, the Verdet constant of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared in Example 1 reached 44.5 rad·m. -1 ·T -1 It is also superior to terbium gallium garnet (Tb3Ga5O) in Comparative Example 1. 12 Crystal 38.8 rad·m -1 ·T-1 This is mainly because the co-doping strategy effectively modulates Tb while achieving charge self-compensation and eliminating defect-induced absorption. 3 + The coordination environment of the ions and the symmetry of the local crystal field significantly improve the probability of magnetic dipole transitions and the magneto-optical response efficiency. This gives it superior application potential in core devices such as Faraday isolators for high-power lasers.
[0074] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A terbium-scandium-aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon, characterized in that, Its molecular formula is (Tb 1- x Ca x )3Sc2(Al 1-z Si z )3O 12 Or Tb3(Sc 1-y Mg y )2(Al 1-z Si z )3O 12 Where x = z, 0 < x < 0.1; 2y = 3z, 0 < y < 0.1; The alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal belongs to the cubic garnet structure with space group Ia-3d; wherein, Ca 2+ Occupying dodecahedral sites, Mg 2+ Occupying the octahedral position, Si 4+ It occupies a tetrahedral position.
2. The method for preparing the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal according to claim 1, characterized in that, Includes the following steps: Based on the molecular formula of the terbium scandium aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon, the raw materials are obtained according to the stoichiometric ratio. The raw materials are mixed evenly, pressed into blocks, and then solid-state sintered to obtain polycrystalline material. Place the polycrystalline material into a crucible and then into a single-crystal furnace. In an oxygen-free atmosphere, heat the material using medium-frequency induction heating until the polycrystalline material melts and the melt is homogeneously mixed. The seed crystal is placed into the melt, and the crystal pulling is completed by sequentially going through crystal pulling, necking, shoulder formation, equal diameter formation and tailing. Once the crystal has grown to the specified size, it is pulled out to detach from the melt, the temperature is lowered to room temperature, and the crystal is removed. After the crystal is cut into devices, it is annealed to obtain a terbium scandium aluminum garnet magneto-optical crystal co-doped with alkaline earth metals and silicon.
3. The preparation method according to claim 2, characterized in that, Based on the molecular formula (Tb) of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal... 1-x Ca x )3Sc2(Al 1-z Si z )3O 12 The raw materials include Tb4O7, Sc2O3, Al2O3, CaCO3, and SiO2; Based on the molecular formula Tb3(Sc) of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal... 1-y Mg y )2(Al 1-z Si z )3O 12 The raw materials include Tb4O7, Sc2O3, Al2O3, MgO and SiO2.
4. The preparation method according to claim 2, characterized in that, The solid-state sintering temperature is 1300~1500℃, and the sintering time is 24~60 h.
5. The preparation method according to claim 2, characterized in that, Medium-frequency induction heating is used until the polycrystalline material melts at a temperature of 1950~2000℃.
6. The preparation method according to claim 2, characterized in that, The seed crystal is <111> Defect-free oriented seed crystals, including terbium scandium aluminum garnet (Tb3Sc2Al3O4). 12 Crystal.
7. The preparation method according to claim 2, characterized in that, During the crystal pulling process, the pulling rate is 0.2~3 mm / h and the rotation speed is 8~30 rpm.
8. The preparation method according to claim 2, characterized in that, During the process of lowering the temperature to room temperature, the cooling rate is 10~80℃ / h.
9. The preparation method according to claim 2, characterized in that, During annealing, the atmosphere is an air atmosphere; Alternatively, during annealing, the temperature is 1300~1500℃, and the annealing time is 20~30 h.
10. The application of the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal according to claim 1, or the alkaline earth metal and silicon co-doped terbium scandium aluminum garnet magneto-optical crystal prepared by the preparation method according to any one of claims 2 to 9, as a magneto-optical device material, includes any one of the following: Used in Faraday isolators; Used in magneto-optical modulation devices; Alternatively, it can function as a magneto-optical crystal that acts as a magneto-optical switch.
Citation Information
Patent Citations
Terbium scandium aluminum garnet, terbium scandium aluminum garnet doped magneto-optical transparent ceramic and preparation method of terbium scandium aluminum garnet doped magneto-optical transparent ceramic
CN111592347A
Calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystal, and preparation method, application and temperature field thereof
CN114250515A